2020
DOI: 10.3390/molecules25204694
|View full text |Cite
|
Sign up to set email alerts
|

Cysteine Sulfoxides Enhance Steroid Hormone Production via Activation of the Protein Kinase A Pathway in Testis-Derived I-10 Tumor Cells

Abstract: Testosterone plays an important role in male sexual characteristics and maturation, and decreased testosterone levels increase the risk of several diseases. Recently, onion extract rich in cysteine sulfoxides, which are amino acids unique to onions, has been reported to alleviate age-related symptoms resulting from decreased testosterone levels in males. However, the mechanism underlying the suppression of low testosterone levels by cysteine sulfoxides has not been elucidated. In this study, we found that onio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…Two pharmacokinetic studies have demonstrated that SAC can metabolize to its N-acetylated form and to a lesser extent its sulfoxide form in rats [ 26 , 43 ]. Although the N-acetylated form of SAC and S -allyl cysteine sulfoxide (alliin) have not been reported to have a steroidogenic effect in vivo or in vitro, structurally similar compounds like propenyl-1-cysteine sulfoxide (isoalliin) and cycloalliin from onion extract have been reported to have a steroidogenic effect in I-10 cells [ 13 ]. Moreover, onion juice, which is rich in cysteine sulfoxides, showed a steroidogenic effect in animal-based experiments [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two pharmacokinetic studies have demonstrated that SAC can metabolize to its N-acetylated form and to a lesser extent its sulfoxide form in rats [ 26 , 43 ]. Although the N-acetylated form of SAC and S -allyl cysteine sulfoxide (alliin) have not been reported to have a steroidogenic effect in vivo or in vitro, structurally similar compounds like propenyl-1-cysteine sulfoxide (isoalliin) and cycloalliin from onion extract have been reported to have a steroidogenic effect in I-10 cells [ 13 ]. Moreover, onion juice, which is rich in cysteine sulfoxides, showed a steroidogenic effect in animal-based experiments [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, its applicability has raised some controversy, as a few cases of cardiovascular events have been reported, followed by TRT [ 8 , 9 ], warranting the search for alternative resources, such as nutritional supplements or natural compounds in diets that have the potential to boost testosterone levels. In this direction, several natural compounds that have the potential to enhance testosterone production either in vitro or in vivo have been explored [ 10 , 11 , 12 , 13 , 14 ]. For instance, vitamin K2 homolog menaquinone-4, geranylgeraniol, and cysteine sulfoxide have been shown to enhance testosterone levels via PKA activation [ 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Testosterone, a steroid hormone, plays a key role in the development of male sexual characteristics, and its reduction may cause infertility (184). It has been reported that onion extractcontained cysteine sulfoxides could stimulate the production of the testosterone precursor, progesterone, by activating the protein kinase A signaling pathway in a testis-derived cell line (I-10) (117). Bacterial infection is one of the main factors that cause infertility in men.…”
Section: Reproductive System Protectionmentioning
confidence: 99%
“…Male hormone replacement has been used to alleviate LOH symptoms but is reported to be associated with several side effects, warranting the need to develop alternative therapies. Vitamins and other dietary ingredients have attracted attention as safe candidates, and some have been reported to increase testosterone production [6][7][8][9][10][11][12][13]. Biotin is a water-soluble vitamin that functions as a cofactor for carboxylases related to the metabolism of carbohydrates, lipids, and amino acids, from microorganisms to higher organisms [14].…”
Section: Introductionmentioning
confidence: 99%